2007
DOI: 10.1073/pnas.0704487104
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific change of unconscious neural priming in the cerebral language network

Abstract: We explored the impact of task context on subliminal neural priming using functional magnetic resonance imaging. The repetition of words during semantic categorization produced activation reduction in the left middle temporal gyrus previously associated with semantic-level representation and dorsal premotor cortex. By contrast, reading aloud produced repetition enhancement in the left inferior parietal lobe associated with print-to-sound conversion and ventral premotor cortex. Analyses of effective connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 37 publications
(48 reference statements)
6
70
0
1
Order By: Relevance
“…Therefore, the instructed task set of the participant required a deep level of information processing (incorporating prefrontal cortex) of the unconscious stimulus. Recently, we (van Gaal et al, 2008) and others (Nakamura et al, 2006(Nakamura et al, , 2007 have shown that the instructed top-down task set strongly determines the processing routes taken by masked stimuli. The combination of both factors allowed us to tap more directly into the possible scope and depth of unconscious information processing than previous studies using the masking task (or related paradigms).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the instructed task set of the participant required a deep level of information processing (incorporating prefrontal cortex) of the unconscious stimulus. Recently, we (van Gaal et al, 2008) and others (Nakamura et al, 2006(Nakamura et al, , 2007 have shown that the instructed top-down task set strongly determines the processing routes taken by masked stimuli. The combination of both factors allowed us to tap more directly into the possible scope and depth of unconscious information processing than previous studies using the masking task (or related paradigms).…”
Section: Discussionmentioning
confidence: 92%
“…Previous behavioral and imaging studies have shown that the way unconscious stimuli are processed is affected by top-down settings of the cognitive system, such as temporal/spatial atten-tion, task strategy and the task being performed (Naccache et al, 2002;Kunde et al, 2003;Sumner et al, 2006;Nakamura et al, 2007). To test whether the relevance of the masked No-Go signal influences the depth to which it is processed, we performed a control experiment, in which the physically identical masked stimulus was task irrelevant (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Opinions however start to deviate when you ask where or when along the chain of processing unconscious sensory information becomes a conscious experience. Some theories make an even more subtle subdivision into unconscious/subliminal, pre-conscious and conscious stages (Dehaene, Changeux, Naccache, Sackur, & Sergent, 2006;Kouider & Dehaene, 2007) or, as mentioned before, into unconscious, phenomenally conscious and access conscious states (Block, 1995(Block, , 1996(Block, , 2005aLamme, 2003Lamme, , 2006Lamme, , 2010. Is this merely a matter of terminology (Block, 2005b)?…”
Section: Consciousness Consensus?mentioning
confidence: 99%
“…On the other hand, the nodes that are in principle active enough to communicate with the workspace neurons (the potential broadcasters) are called 'preconscious' . They are thought to require an attentional boost to become part of the network that involves the workspace neurons and constitutes (access) consciousness (Dehaene, Changeux, Naccache, Sackur, & Sergent, 2006;Kouider & Dehaene, 2007). As such, the preconscious nodes can perhaps be thought of as constituting phenomenal consciousness.…”
Section: Global (Neuronal) Workpace Theorymentioning
confidence: 99%
See 1 more Smart Citation